HOW TO AVEID PL - Nargiza Botirovna Abdullayeva (TADQIQOTLAR, 2026)
Annotation This article discusses the concept of plagiarism, its negative impact on the educational process, and effective ways to avoid it. The importance of independent thinking, proper use of sources, citation rules, and paraphrasing techniques in writing scientific papers and articles is also analyzed. In addition, the article presents modern methods and recommendations for preventing plagiarism.